Body fatness in relation to physical activity and selected socioeconomic parameters of adolescents aged 15–17 years in Merida, Yucatan. (November 2014) - Datta Banik, Sudip; Castillo, Teresa; Rodriguez, Luis; Dickinson, Federico
Abstract Background: Increasing rates of overweight and obesity in adolescents are major concerns in many countries, including Mexico. Objectives: To study anthropometric and body composition characteristics (BCC) and their relations with socioeconomic status (SES), biological history and physical activity (PA) of school-going adolescent boys and girls in the city of Merida, Yucatan, Mexico. Subjects and methods: In this cross-sectional study, a sample of 321 adolescents (156 boys and 165 girls) aged 15–17 years from public and private schools in Merida, was taken from a study carried out in 2008–2009. Results: Body mass index had significant correlations to BCC (fat mass and fat-free mass). The rate of stunting was higher in girls (18.20%) than in boys (7.69%). Stunted adolescents had higher body fat (%) than normally growing peers. High rates of overweight (boys 26.28%, girls 24.24%) and obesity (boys 10.26%, girls 6.06%) were recorded. SES (parents' age, education and occupation; crowding index in the family; household food expenditure), participants' biological history and PA are related with height and BCC by age and sex. Conclusion: Adolescents with excess weight (overweight + obesity) reported being less physically active. SES and PA were strongly related to growth and body fatness in the studied adolescents.